Knowledge Management through Lessons Learned from Family Case Mediation by Juvenile and Family Case Mediators in the Juvenile and Family Court in Samut Sakhon Province - Termpinijtham , Anchalee; Angasinha , Chatwarun (Journal of Dhamma for Life, 2025)
This research aims to study the knowledge management of reconciliation of youth and family cases by extracting mediation lessons from family mediators in the Juvenile and Family Court, Samut Sakhon Province, and propose guidelines for reconciliation of juvenile and family cases in the Juvenile and Family Court. A qualitative study method was used as data were collected through 7 family mediators and lessons learned from knowledge management in 12 cases using in-depth interviews. The results of the study found that the mediation process in family cases consisted of (1) preparing before negotiations; (2) creating a friendliness and trust atmosphere; (3) compromise negotiation; (4) proposing alternatives and finding mutually acceptable solutions; and (5) making agreements and monitoring the results. There were many important principles in compromising, including (1) building confidence and trust; (2) displaying appropriate body language and communication; (3) summarizing and reiterating the understandings; and (4) asking thought-provoking questions. For guidelines for reconciling youth and family cases that lead to successful results, they consisted of (1) the mediator must be prepared; (2) well management of the immediate situation; (3) appropriate exhibition; and (4) having negotiation skills. Moreover, the mediator role that led to failure arose from internal or external factors that affected the mediation process. The suggestions included (1) amending the law to be consistent with the principles of individual rights and freedoms; (2) adding regulations regarding reconciliation of family cases to be clearer; (3) improving and amending the qualifications of family mediators to be suitable for performing their duties; and (4) providing regular training to mediators in family cases.